State- and County-Level Social Capital as Predictors of County-Level Suicide Rates in the United States: A Lagged Multilevel Study. (September 2021) - Dev, Saloni; Kim, Daniel
From 1999 through 2017, age-adjusted suicide rates in the United States rose by 33% (from 10.5 to 14.0 per 100 000 population). Social capital, a key social determinant of health, could protect against suicide, but empirical evidence on this association is limited. Using multilevel data from the Centers for Disease Control and Prevention, we explored state- and county-level social capital as predictors of age-adjusted suicide rates pooled from 2010 through 2017 across 2112 US counties. In addition, we tested for causal mediation of these associations by state-level prevalence of depression. A 1-standard deviation increase in state-level social capital predicted lower county-level suicide mortality rates almost 2 decades later (0.87 fewer suicides per 100 000 population; P = .04). This association was present among non-Hispanic Black people and among men but not among non-Hispanic White people and women. We also found evidence of partial mediation by prevalence of depression. Our findings suggest that elevating state- and county-level social capital, such as through policy and local initiatives, may help to reverse the trend of rising suicide rates in the United States.